Accounting Scholarship that Advances Professional Knowledge and Practice - Kaplan, Robert S. (The Accounting Review, 2011)
ABSTRACT: Recent accounting scholarship has used statistical analyses on asset prices, financial reports and disclosures, laboratory experiments, and surveys of practice. The research has studied the interface among accounting information, capital markets, standard-setters, and financial analysts and how managers make accounting choices. But as accounting scholars have focused on understanding how markets and users process accounting data, they have distanced themselves from the accounting process itself. Accounting scholarship has failed to address important measurement and valuation issues that have arisen in the past 40 years of practice. This gap is illustrated with missed opportunities in risk measurement and management and the estimation of the fair value of complex financial securities. This commentary encourages accounting scholars to devote more resources to obtaining a fundamental understanding of contemporary and future practice and how analytic tools and contemporary advances in accounting and related disciplines can be deployed to improve the professional practice of accounting.